(untitled) (Journal of Dhaka National Medical College & Hospital, 2023)
Foreign bodies in the ear are relatively common in emergency medicine. However, attempts at removal made outside the health care setting by untrained persons can result in complications of varying degree. The current study was a descriptive type of cross-sectional study that was conducted for 3 years from February 2020 to January 2023. The study included 123 cases in both sexes. The technique used in the study was convenient type of non-probability sampling. Among the respondents 80 were males and 43 were females. The incidence of an aural foreign body was directly proportional to age group (0-5) years are higher (43.1%) than other. The most common foreign bodies were stone (22.8%). paper (16.3%) . beads (14.6%), eraser (12.2%) and cotton buds (11.4%). Out of 123 patients 93 patients went to the otolaryngologist for foreign body insertion. But other 30 patients went to non-otolaryngologist and all of them were suffered from different type of complication. Such as 17 cases of canal abrasion, laceration, and/or bleeding, 8 cases of otitis externa, 6 cases of tympanic membrane perforation, 5 cases of impaired hearing. 3 cases of chronic suppurative otitis media, and 2 cases of middle ear involvement. Of the 93 patients who were seen by an otolaryngologist initially, only 6 (6.5%) developed a complication: 4 cases of canal abrasion. laceration, and/or bleeding and 2 cases of otitis externa. The difference in overall complication rates between patients treated by otolaryngologists and non-otolaryngologists was statistically significant (p<0.001). We conclude that attempts at removal of foreign body by otolaryngologists can reduce the incidence of complications. J. Dhaka National Med. Coll. Hos. 2023; 29 (02): 42-46